Determination of Radial Growth in Selected Tropical Tree Species Using Pinning Method and Dendrometer - Zarnudin, Norline (2010)
Radial growths of Shorea leprosula (Meranti tembaga), Hopea odorata (Merawan siput jantan), Shorea parvifolia (Meranti sarang punai) and Endospermum malaccense (Sesenduk), growing under humid tropics in Selangor was studied in a one year period. The objectives of this study were to investigate the radial growth increment of the above species through dendrometer and pinning methods. Meteorological data of the experimental sites for one year period were also obtained. In this method, a comparison of vessel and ray width before and after the wounding was carried out. Average vessel diameter changed from large to the small diameter. However average ray width changed from small to a large diameter once when a pin was inserted. In S. leprosula average vessel diameter changed from 238 to 104 μm. Average vessel diameter of H. odorata changed from 203 to 128 μm. Ray’s width changed from 44 to 58 μm in S. leprosula and 43 to 54 μm in H. odorata. Through the pinning experiment radial growth of all selected tree species was obtained. Traumatic resin canals (TRC) usually occur sporadically due to injury in concentric formation formed in dipterocarp species. Measurement of the length of TRC in a tangential direction was obtained. In S. leprosula tangential length was 38.6 mm and average diameter of TRC was 86.7 μm (in normal wood, average diameter of resin canal was 53.4 μm). In H. odorata tangential length of TRC was 25.6 mm while diameter was 31.4 μm. Correlation between monthly radial growths with meteorological data was investigated. From the experiments, S. leprosula and S. parvifolia have the correlation coefficient in a range of 0.3. This phenomenon is considering S. leprosula, S. parvifolia and E. malaccense species correlated significantly with precipitation. The correlation between monthly radial growth and precipitation indicates a general positive relationship. The study concluded that the dendrometer and pinning method was appeared to be a simple and effective method to measure the radial growth changes in these tropical trees.